The inclusion of zinc amino acid complex in Nile tilapia diets can reduce the dietary crude protein content: Growth performance, carcass composition, nutrient retention, and hematobiochemical status - Crislaine Palmeira Barbosa de Oliveira; Carlos Eduardo Copatti; Carlos Henrique da Paixão Lemos; Ricardo David Couto; Claudia Figueiredo-Silva; Janilson Felix da Silva; Adailton Thiago Silva dos Santos; Geovana Dotta; Luiz Vitor Oliveira Vidal (Aquaculture Reports)
This study aimed to evaluate the effects of dietary supplementation with zinc amino acid complex (ZnAA) in reduced crude protein extruded diets for Nile tilapia juveniles. Fish (41.55 g) were fed on a regime of apparent satiety in a randomized design (seven treatments and three repetitions) in 250 L tanks for 63 days. There were two control diets (no ZnAA), which were categorized as positive control (crude protein content of 318.90 g kg−1, estimated 264.52 g kg−1 of digestible protein) and negative control (low crude protein content of 248.32 g kg−1, estimated 200.90 g kg−1 of digestible protein). Another five experimental diets with mean reduced low crude protein content (243.08 g kg−1, estimated 196.17 g kg−1 of digestible protein) with 20, 40, 60, 80, and 100 mg ZnAA kg−1 were also tested. Carcass composition, nutrient retention, and zootechnical, hematological, and biochemical responses were evaluated. The negative control, 40, 80, and 100 mg ZnAA kg diet−1 treatments showed similar growth performance to the positive control. Carcass lipid values and nitrogen retention were lower in the positive control. An increase in dietary ZnAA augmented phosphorus concentration and retention and Zn concentration. The Zn retention was higher in the negative control. Plasma glucose levels and plasma and liver aspartate aminotransferase activity were higher in the positive control. Plasma high-density lipoprotein cholesterol levels were lower in the negative control. Total leukocytes were increased in 80 and 100 mg ZnAA kg diet−1 treatments. In conclusion, it is recommended to reduce the crude protein content in Nile tilapia extruded diets from 295 to 264 g kg−1, incorporating 80 mg ZnAA kg diet−1, since it can contribute to carcass composition and hematobiochemical parameters without harming the fish growth.